2022
DOI: 10.1039/d2ay00569g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the magnetic field produced by a Halbach array magnetizer on water UV absorption, removal of scale and change in calcium carbonate polymorphs

Abstract: According to the UV absorption, scale removal, and aragonite CaCO3 proportion results, the dual Halbach array magnetizer exhibited the highest magnetic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…1 However, Chuchai Sronsri (2022) demonstrated the influence of the magnetic field, generated by a laboratory-scale double Halbach magnetizer, on the ultraviolet (UV) absorption of water flowing through three magnetic configurations where the field induction B = (380-580) mT varies. 2 In agriculture, the action of magnetically treated water has been reported; to accelerate the growth, germination and nutrient absorption of plants, gaining more momentum, due to its positive action at an experimental and agro-industrial level. [3][4][5] In the industrial branch, the use of magnetism has been reported in sugar mills, derivative plants (distilleries), artificial bagasse wood factories, wax factories, and others.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, Chuchai Sronsri (2022) demonstrated the influence of the magnetic field, generated by a laboratory-scale double Halbach magnetizer, on the ultraviolet (UV) absorption of water flowing through three magnetic configurations where the field induction B = (380-580) mT varies. 2 In agriculture, the action of magnetically treated water has been reported; to accelerate the growth, germination and nutrient absorption of plants, gaining more momentum, due to its positive action at an experimental and agro-industrial level. [3][4][5] In the industrial branch, the use of magnetism has been reported in sugar mills, derivative plants (distilleries), artificial bagasse wood factories, wax factories, and others.…”
Section: Introductionmentioning
confidence: 99%